2018
DOI: 10.1007/s13304-018-0607-4
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and indications for emergency thoracotomy after adoption of a more liberal policy in a western European level 1 trauma centre: 8-year experience

Abstract: The role of emergency thoracotomy (ET) in blunt trauma is still a matter of debate and in Europe only a small number of studies have been published. We report our experience about ET both in penetrating and blunt trauma, discussing indications, outcomes and proposing an algorithm for patient selection. We retrospectively analysed patients who underwent ET at Maggiore Hospital Trauma Center over two periods: from January 1st, 2010 to December 31st, 2012, and from January 1st, 2013 to May 31st, 2017. Demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…However, it has been repeatedly shown that RT can be significantly morbid and is resource intensive. [1][2][3] With recent advances and enthusiasm in endovascular interventions to control NCTH, an increasing number of research studies, mainly in a retrospective manner, have examined the use of the resuscitative endovascular occlusion of the aorta (REBOA) for severely injured patients as an alternative method of AO. [4][5][6] To date, multiple studies in Japan and the United States using the nationwide database have failed to demonstrate outcome benefits related to the use of REBOA.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been repeatedly shown that RT can be significantly morbid and is resource intensive. [1][2][3] With recent advances and enthusiasm in endovascular interventions to control NCTH, an increasing number of research studies, mainly in a retrospective manner, have examined the use of the resuscitative endovascular occlusion of the aorta (REBOA) for severely injured patients as an alternative method of AO. [4][5][6] To date, multiple studies in Japan and the United States using the nationwide database have failed to demonstrate outcome benefits related to the use of REBOA.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Similarly, western Europe has also seen a greater proportion of EDTs performed for blunt trauma. [ 14 ] We did not have the ability to identify if EDT was performed for nontraumatic injuries, as EDT is becoming expanded to other conditions. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Resuscitative endovascular balloon occlusion of the aorta (REBOA) has been developed to control hemodynamically unstable hemorrhagic shock patients and to maintain brain and coronary perfusion [4,5]. Emergency resuscitative thoracotomy (ERT), which was previously performed, can be indicated for a single penetrating injury; however, for blunt injuries, there are many debates on performing ERT [6]. Some authors argue that REBOA can replace ERT in select cases [4,7].…”
Section: Introductionmentioning
confidence: 99%